TGF-β enhances the cytotoxic activity of Vδ2 T cells. (2nd January 2019) - Peters, Christian; Meyer, Annika; Kouakanou, Léonce; Feder, Julia; Schricker, Tim; Lettau, Marcus; Janssen, Ottmar; Wesch, Daniela; Kabelitz, Dieter
ABSTRACT: TGF-β is a pleiotropic cytokine with multiple roles in immunity. Apart from its suppressive activity, TGF-β is a driving cytokine in the differentiation of induced regulatory T cells (iTreg) but also in the polarization of interleukin-9 (IL-9) producing T helper 9 (Th9) T cells. Human Vδ2 expressing γδ T cells exert potent cytotoxicity towards a variety of solid tumor and leukemia/lymphoma target cells and thus are in the focus of current strategies to develop cell-based immunotherapies. Here we report that TGF-β unexpectedly augments the cytotoxic effector activity of short-term expanded Vδ2 T cells when purified γδ T cells are activated with specific pyrophosphate antigens and IL-2 or IL-15 in the presence of TGF-β. TGF-β up-regulates the expression of CD54, CD103, interferon-γ, IL-9 and granzyme B in γδ T cells while CD56 and CD11a/CD18 are down-regulated. Moreover, we show that CD103 (αE/β7 integrin) is recruited to the immunological synapse in γδ T cells. Increased cytotoxic activity of TGF-β-exposed γδ T cells is reduced by anti-CD103 and further diminished upon additional anti-CD11a antibody treatment, pointing to a role of cellular adhesion in the enhanced cytolytic activity. Furthermore, magnetically sorted CD103-positive Vδ2 T cells exhibit superior cytolytic activity. In view of the importance of CD103 for tissue homing of lymphocytes, our results suggest that adoptive transfer of CD103-expressing Vδ2 T cells might favor their homing to solid tumors.